Estudio doctrinario jurídico del principio non bis in ídem y su incidencia en los delitos de lavado de activos - Solano Mendoza, Cesar Alberto (Machala, 2021)
The present investigative work, is carried out under the Complexive Exam modality practical part, having to emphasize that the hypothetical case chosen focuses on the criminal and constitutional field since it is about the meticulous analysis of the admissibility or inadmissibility of a double accusation by the prosecution, when discovering in the investigations that Rasputin has carried out unusual transactions. In addition, the investigation showed that the funds would come from the crime of tax fraud. For the above stated the objective of this investigation is to determine the scope of the applicability of the non bis in idem principle in the criminal proceedings in relation to the crime of money laundering through doctrinal and legal bases. Furthermore, given that the crime money laundering is complex both in its nature and in its process, it is will be addressing the evolution of this crime according to the growth of the delinquency, its particularities and the theories that sustain the nature of its autonomy compared to other criminal typologies contemplated in the comprehensive organic criminal Code. The methodology used is structured from a qualitative perspective applying a documentary investigation, the scientific methods chosen for carrying out the investigative are: Analytic, Systematic, Deductive, Inductive and Exegetical. With the support of these investigative elements and the support of doctrinal postulates and legal arguments, it will be possible to arrive at a feasible solution to the exposed hypothesis, which will be presented in the conclusions of the topic.
El presente Trabajo Investigativo , se realiza bajo la modalidad Examen Complexivo parte práctica, debiendo recalcar que el caso hipotético escogido se centra en el ámbito penal y constitucional ya que se trata del análisis minucioso de la procedencia o improcedencia de una doble imputación por parte de fiscalía, al descubrir en sus investigaciones que Rasputín ha realizado transacciones financieras inusuales, además la investigación arrojo como resultado que dichos fondos provendrían del delito de defraudación tributaria. Por lo antes expuesto, el objetivo de esta investigación es determinar el alcance de la aplicabilidad del principio non bis in ídem en los procesos penales, con relación al delito de lavado de activos mediante bases doctrinarias y jurídicas. Adicionalmente, dado que el delito de lavado de activos es complejo tanto en su naturaleza como en su proceso, se abordará la evolución que ha tenido este delito acorde al crecimiento de la delictividad, sus particularidades y las teorías que fundamentan la naturaleza de su autonomía frente a otros tipos penales contemplados en el Código orgánico integral penal. La Metodología empleada se estructura desde una perspectiva cualitativa aplicando una investigación documental, los métodos científicos elegidos para la realización del trabajo investigativo son: Analítico, Sistemático, Deductivo, Inductivo y Exegético. Con el apoyo de estos elementos investigativos y el soporte de los postulados doctrinarios y sustentos jurídicos, se podrá llegar a una solucion factible a la hipótesis expuesta, la cual será presentada en las conclusiones del tema.
Keywords: NON BIS IN IDEM; SEGURIDAD JURIDICA; DELITO; TRANSACCION SOSPECHOSA